If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 9) = 93 Reorder the terms: 3(9 + 2x) = 93 (9 * 3 + 2x * 3) = 93 (27 + 6x) = 93 Solving 27 + 6x = 93 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 6x = 93 + -27 Combine like terms: 27 + -27 = 0 0 + 6x = 93 + -27 6x = 93 + -27 Combine like terms: 93 + -27 = 66 6x = 66 Divide each side by '6'. x = 11 Simplifying x = 11
| (6x-3+8)=(3x+10-x) | | 15x=27 | | 6(6+4n)=-n-14 | | x+2=4x-2 | | y+9x=3x | | h=-16t^2+80t+25 | | 66+20p=30p-14+10 | | X^2=x+56+y | | 32=4q | | 86-5x=26 | | 9x+14=2(x+14) | | 6+y=23 | | N-3=n-1 | | V/3-1=-14 | | 12x-7=2(4x+7) | | -2y+3y+5y=-18 | | sinx+2cos^2x=2 | | 5/x(3-x)/2 | | 144=12a | | sinx+2con^2x=2 | | M+1=2m-2m-7 | | t=log(5)9 | | X^2+6x+16=39 | | 9(y-5)=4y-10 | | 2x-7+8x+10+82=180 | | 8y-5y=67 | | 32x+11y=291 | | xdy-y+xy^3(1+lnx)dx=0 | | -19+32m=37m-39 | | 14x-21y= | | 9x^2+12x^2=cx^2 | | 9x+7=x+7 |